COVID-19: Multidisciplinary Studies on the Thyroid Activity During the Pandemic and Post-Covid Processes - Ryabukha, Ольга (Actual Problems of Medicine and Pharmacy, 2022)
In the current global spread of the COVID-19 pandemic, which is observed among all segments of the population, the thyroid gland can play a leading role in both the clinical course of the disease and in the processes of post-covidal recovery of human functional activity. It is multidisciplinary research that covers such areas as medicine, mathematics, pharmacy, law, etc., confirms the importance of the thyroid gland to ensure vital functions. In this case, the disclosure of the deep essence of the processes occurring in it in the norm and pathology is possible on the basis of innovative use of correlation analysis with the designing of correlation portraits of the main follicular thyrocytes' activities.